Nucleation Study on Deposition of Aluminum from 1-Butyl-3-Methylimidazolium Chloride and Aluminum Chloride Ionic Liquid Electrolyte. (8th September 2020) - Peng, Yuxiang; Shinde, Pravin; Reddy, Ramana G.
Abstract : The aluminum is electrodeposited from an ionic liquid comprising a eutectic mixture of 1-butyl-3-methylimidazolium chloride (BMIC) and aluminum chloride (AlCl3 ) at the AlCl3 mole fraction of 0.667 (molar ratio of 1:2). The electrochemical behavior of chloroaluminate species in the ionic liquid (IL) is investigated by the chronoamperometry (CA) technique at different temperatures. The diffusion coefficients ( D ) of Al2 Cl7 – anion species in BMIC-AlCl3 IL are calculated at various temperatures based on the chronoamperometric method. The calculated number density of nucleation of Al deposits are 0.7 × 10 10, 1.0 × 10 10, and 1.4 × 10 10 m -2 at 363 K with the applied potentials of -1.7, -1.75, and -1.8 V versus Pt, respectively. The scanning electron microscopy (SEM) result indicated that the calculated data is comparable to the experimental electrodeposition data. In addition, the rate of nucleation was also investigated during the electrodeposition experiment.